The Effect Of Independence, Due Professional Care, And Audit Intensity On Audit Quality (Case Study At A Public Accounting Firm In Indonesia During The Covid-19 Pandemic) - Pramesti, Nataza Intan; Saputro, Julianto Agung; Kusuma, Manggar Wulan (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
The aims of this research are to describe the influence of: (1) influence of independence on audit quality in public accountant firms Indonesia. (2) influence of due professional care on audit quality in public accountant firms Indonesia. (3) influence of intensity examination on audit quality in public accountant firms Indonesia. Types of data on this research is primary data in the form of a questionnaire. Population of the research is an auditor who worked the public accountant and work from home during pandemic covid-19. Convenience sampling methods used is obtained from 118 respondents. From 133 questionnaires that were collected, there are 15 data cannot be used. Test requirements analysis included tests for normality, linearity test multicolinearity test, and heteroscedasticity test. The result of the research show that: (1) There is no effect between independence on audit quality, it proved by tcount, smaller than ttable namely 1,248 < 1,98 and the value of significance of 0,215 > 0,05. (2) There is significant effect between due professional care on audit quality, it proved by tcount larger than ttable namely 2,946 > 1,98 and the value of significance of 0.004 < 0,05. (3) There is significant effect between intensity examination on audit quality, it proved by tcount larger than ttable namely 4,244 > 1,98 and the value of significance of 0.000 < 0,05.